2018
DOI: 10.1159/000489683
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of S100A4 Alleviates Cardiac Fibrosis via Wnt/β -Catenin Pathway in Mice

Abstract: Background/Aims: Cardiac fibrosis is a pathological change leading to cardiac remodeling during the progression of myocardial ischemic diseases, and its therapeutic strategy remains to be explored. S100A4, a calcium-binding protein, participates in fibrotic diseases with an unclear mechanism. This study aimed to investigate the role of S100A4 in cardiac fibrosis. Methods: Cardiac fibroblasts from neonatal C57BL/6 mouse hearts were isolated and cultured. Myocardial infarction was induced by ligating the left an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Together these results show that S100A4 overexpression led to a decreased activation of the fetal gene programm in our EHTs. Both findings, i.e., reduced steady state mRNA levels of mediators of fibrosis and hypertrophy are in line with recently reported data from Doroudgar and colleagues, who have shown more adverse fibrotic remodeling, more post-ischemic damage and increased Nppa and Nppb transcription in S100A4 KO mice (Doroudgar et al, 2016 ) and from Qian and colleagues, who have shown that siRNA-mediated downregulation of S100A4 alleviates cardiac fibrosis after LAD-ligation in mice (Qian et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Together these results show that S100A4 overexpression led to a decreased activation of the fetal gene programm in our EHTs. Both findings, i.e., reduced steady state mRNA levels of mediators of fibrosis and hypertrophy are in line with recently reported data from Doroudgar and colleagues, who have shown more adverse fibrotic remodeling, more post-ischemic damage and increased Nppa and Nppb transcription in S100A4 KO mice (Doroudgar et al, 2016 ) and from Qian and colleagues, who have shown that siRNA-mediated downregulation of S100A4 alleviates cardiac fibrosis after LAD-ligation in mice (Qian et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…26 However, its association with hypoxic CFs has yet to be investigated. Consistent with a previous study, 27 our results showed that β-catenin expression was elevated in CFs exposed to hypoxia ( Figure 6A-C), and this was accompanied by a greater ability to migrate and higher proliferation capacity ( Figure 4F-H). Furthermore, Xiang et al 28 demonstrated that the loss of β-catenin in mouse CFs attenuated cardiac fibrosis induced by pressure overload.…”
Section: Mir-145 and Sox9 Exert Their Effects By Regulating The Aktsupporting
confidence: 93%
“…Recent studies also directly demonstrated recombinant S100A4 protein elicited a robust hypertrophic response in cardiac myocytes, with an increased number of viable cells and inhibited apoptosis . Knockdown of S100A4 was reported to significantly suppress proliferation of cardiac fibroblasts and collagen expressions and thus could alleviate cardiac fibrosis . These findings suggested S100A4 may be potentially important for the pathogenesis of VMC.…”
Section: Discussionmentioning
confidence: 99%
“…28 Knockdown of S100A4 was reported to significantly suppress proliferation of cardiac fibroblasts and collagen expressions and thus could alleviate cardiac fibrosis. 13,29 These findings suggested S100A4 may be potentially important for the pathogenesis of VMC. In accordance with these studies, our present results, for the first time, showed that the expressions of S100A4 at mRNA and protein levels were significantly increased in VMC group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%